PENGARUH ISOPROPIL MYRISTAT SEBAGAI BAHAN PENINGKAT PENETRASI TERHADAP LAJU DIFUSI KRIM PEMUTIH EKSTRAK ETANOL DAUN MURBEI (Morus alba L) - Nurul Arfiyanti Yusuf; Aisyah Fatmawaty (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
The research has conducted research on the effectiveness of isopropyl myristat as a penetration enhancer on the diffusion rate of whitening cream mulberry leaf extract (Morus alba L) in vitro. This study aims to determine the effect of the use of isopropyl myristat. Mulberry leaf extract cream made with varying concentrations respectively 3%, 4%, 5% Isopropyl myristat as penetration enhancers made into 3 formulas (F1-F4) with the F1 without penetration enhancers. Evaluation of stability before and after accelerated storage includes observation of the organoleptic, emulsion type determination, measurement of pH, and viscosity. The evaluation results indicate four physically stable formula. In vitro diffusion studies conducted by Franz diffusion cells and footage is measured at a wavelength of 367.4 nm. The results of diffusion studies show that formula with the highest diffusion rate of 0.024 µg/minute on F4 (5% isopropyl myristat).